FOODAlyzer usability: Advances in food safety education - Wen-Li Seow; Kai Wei Lee; Roshariza Haris; Umi Kalsom Md Ariffin; Shing Wei Ng; Sook Yee Lim; Madihah Mohd Saudi; Abdul Rahman Mohamad Gobil; Nurul Azmawati Mohamed @ Abd Aziz; Nor Afiah Mohd Zulkefli; Tengku Zetty Maztura Tengku Jamaluddin; Noris Mohd Norowi; et al. (Public Library of Science (PLoS), 2025)
Indexed Publication (Tier 2)